2008
DOI: 10.1007/s10535-008-0088-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved in vitro rooting of Prunus dulcis Mill. cultivars

Abstract: A highly reproducible system was developed for efficient rooting of cultivars Boa Casta (BC) and Peneda and a BC seedling-derived clone (BC VII) of almond (Prunus dulcis Mill.). Twenty-four accessions derived from the clone BC VII and subjected to various in vitro culture treatments were screened. The long induction pre-treatment (LIP, 5 d), the brief induction pre-treatment (BIP, 16 h) and the hormonal shock by short dipping in hormone solution (1 min), were tested. BIP was the only that allowed rooting of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…The experiments were arranged in a completely randomized design and each experiment was repeated twice. Percentage data were arcsin transformed to validate the one-way analysis of variance (ANOVA) assumption of normality of data distribution (Tereso et al 2008), and then subjected to statistical analysis. For all the tested parameters ANOVA was used to find differences among treatments, Duncan Multiple Range Test for separating mean values and significant effects were accepted at P B 0.05.…”
Section: Experimentation and Data Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The experiments were arranged in a completely randomized design and each experiment was repeated twice. Percentage data were arcsin transformed to validate the one-way analysis of variance (ANOVA) assumption of normality of data distribution (Tereso et al 2008), and then subjected to statistical analysis. For all the tested parameters ANOVA was used to find differences among treatments, Duncan Multiple Range Test for separating mean values and significant effects were accepted at P B 0.05.…”
Section: Experimentation and Data Analysismentioning
confidence: 99%
“…New emerging evidence further suggests that part of the effects of IBA are caused solely by its direct action (Ludwig-Müller et al 2005), and this may partially account for the differences in rooting abilities observed in this study. Tereso et al (2008) attributed the differential rooting abilities of auxins to differences in affinity for the auxin receptors involved in the rhizogenic process.…”
Section: Shoot Induction In Hypocotyls and Epicotylsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rooting difficulties occur in micropropagation of plants belonging to Prunus genus (Gonzales Padilla et al 2003;Š tefančič et al 2005;Tereso et al 2008). Shoots of both fruit-bearing and ornamental species are considerably easily multiplicated in vitro (Nowak and Miczyński 2002;Kalinina and Brown 2007;Petri and Scorza 2010), while root formation remains problematic.…”
Section: Introductionmentioning
confidence: 99%